文化霸权与新加坡华文教育: 以南洋大学为例 = Cultural hegemony and chinese education in Singapore : Nanyang University as a case study - 赖思延 Lai, Siyan (2013)
本文以南洋大学为个案，以葛兰西的文化霸权为角度，重新诠释南洋大学与各时期的新加坡政府之间错综复杂的关系，并以此观照南洋大学的文化霸权角色如何影响新加坡华文教育在二战后的发展。本文的第一部分侧重分析南洋大学在殖民时期与后殖民时期背后的文化霸权色彩以及南洋大学在文化霸权架构中的对象角色。第二部分则进一步论述南洋大学在文化霸权架构中的媒介角色，通过文化霸权的视角，了解南洋大学对华语社群意识形态的牵涉，间接成为新加坡华文教育加速衰弱的其中根源。本文的第三部分则以葛兰西对霸权主义演化与进阶的诠释为中心，分析英殖民政府与新加坡政府对新加坡华文教育的霸权色彩，进而了解原本蓬勃发展的华文教育如何在霸权操作的笼罩下走向没落。本文的三个部分以文化霸权理论论述南洋大学的文化霸权对象与媒介的角色，南洋大学的文化霸权角色招致自身的没落，同时也牵动着华语社群的意识形态重塑，间接加速了新加坡华文教育的衰弱。Using Antonio Gramsci’s cultural hegemony framework as a viewpoint, this paper would adopt Nanyang University as a case study to reinterpret the relations between Nanyang University and the dominating authorities in different ruling periods, thereby demonstrating the effects of Nanyang University’s hegemonistic roles on the development of Singapore Chinese education post World War II. The paper first focuses on analyzing the hegemonistic trail in Nanyang University during both the British colonial rule and post-colonial rule, disserting the role of Nanyang University as a target of cultural hegemony. The second part of the paper further elaborates the cloaked role of Nanyang University as a medium of cultural hegemony, aiding in the acceleration of ideology restructuring within the Chinese-speaking community in Singapore which indirectly led to the downfall of Chinese education in Singapore. Lastly, by addressing Antonio Gramsci’s observation on the evolution of hegemony, the third part analyzes the hegemonistic means of the British colonial government and the Singapore government towards the Chinese education in Singapore, thereby understanding the decadence of Chinese education under the cultural hegemony envelopment. Through these demonstrations, this thesis hopes discourse the hegemonistic roles of Nanyang University in the cultural hegemony framework, and how it’s roles would hasten the retreat of Chinese education in Singapore.